Similarities between acylcarnitine profiles in large for gestational age newborns and obesity. Issue 1 (December 2017) - Sánchez-Pintos, Paula; de Castro, Maria-Jose; Roca, Iria; Rite, Segundo; López, Miguel; Couce, Maria-Luz
Abstract Large for gestational age (LGA) newborns have an increased risk of obesity, insulin resistance, and metabolic syndrome. Acylcarnitine profiles in obese children and adults are characterized by increased levels of C3, C5, and certain medium-chain (C12) and long-chain (C14:1 and C16) acylcarnitines. C2 is also increased in insulin-resistant states. In this 1-year observational study of 2514 newborns (246 LGA newborns, 250 small for gestational age (GA) newborns, and 2018 appropriate for GA newborns), we analyzed and compared postnatal acylcarnitine profiles in LGA newborns with profiles described for obese individuals. Acylcarnitine analysis was performed by tandem mass spectrometry on dried- blood spots collected on day 3 of life. LGA newborns had higher levels of total short-chain acylcarnitines (p < 0.001), C2 (p < 0.01) and C3 (p < 0.001) acylcarnitines, and all C12, C14, and C16 acylcarnitines except C12:1. They also had a higher tendency towards carnitine insufficiency (p < 0.05) and carnitine deficiency (p < 0.001). No significant differences were observed between LGA newborns born to mothers with or without a history of gestational diabetes. This novel study describes a postnatal acylcarnitine profile in LGA with higher levels of C2, C3, total acylcarnitines, and total short-chain acylcarnitines that is characteristic of childhood and adult obesity and linked to an unhealthy metabolic phenotype.